Korzyści z prywatyzacji SPZOZ - wynik doświadczeń praktycznych - Bokiej, Beata (Benefits SPZOZ Privatization - Practical Experience, 2006)
Going, in the last time, system changes in the sphere of the health care policy in Poland, enable to rise new economic subjects in the independent, non-public sector. These subjects were adopted to conditions of services dominating on the medical market perfectly . The part of non-public health care entities rose of transformations "privatization" of independent public health care entities, the part are totally new medical companies. From the perspective of events already made, it is intentional examining if reconstructing action taken up brought noticeable benefits for patients, workers of these units and institutions supervising them. In this article the author is making identification of potential and actual benefits and is judging their scale from the point of the view of each participants in the system.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1103, s. 71-84